2005
DOI: 10.1212/01.wnl.0000156522.93403.c3
|View full text |Cite
|
Sign up to set email alerts
|

Role of cerebral amyloid angiopathy in intracerebral hemorrhage in hypertensive patients

Abstract: Cerebral amyloid angiopathy plays a major role in the pathogenesis of intracerebral hemorrhage even in patients with more evident risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 28 publications
(51 reference statements)
4
79
0
2
Order By: Relevance
“…8,20 A recent autopsy study showed that severe hypertension was related to nonlobar, but not to lobar PICH. 9 Our results suggest that elevated blood pressure is related to both PICH subtypes, in particular nonlobar PICH, both in terms of absolute and relative risks. This is in line with the results of a recent meta-analysis 21 in which, however, only qualitative data on prestroke hypertension, in most cases established after a stroke event, was available.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…8,20 A recent autopsy study showed that severe hypertension was related to nonlobar, but not to lobar PICH. 9 Our results suggest that elevated blood pressure is related to both PICH subtypes, in particular nonlobar PICH, both in terms of absolute and relative risks. This is in line with the results of a recent meta-analysis 21 in which, however, only qualitative data on prestroke hypertension, in most cases established after a stroke event, was available.…”
Section: Discussionmentioning
confidence: 60%
“…8 However, most previous studies in this field are case-control studies 7,8 or studies that only include fatal cases. 9,10 Here, we have prospectively studied the effects of hypertension on the absolute and relative risks of ischemic stroke, PICH, and PICH with lobar and nonlobar location.…”
mentioning
confidence: 99%
“…In addition to the possibility that patients concomitantly had CAA and HA, 22 our findings indicate the possibility that clinical differentiation between CAA and HA is not straightforward in some cases of ICH. The classification accuracy of HA and CAA based on hemorrhage patterns in brain images has been reported to be only 66.8%.…”
Section: Discussionmentioning
confidence: 70%
“…32 A second postmortem study in hypertensive patients similarly demonstrated that CAA was associated with not only lobar but also deep brain hemorrhage. 33 These findings indicate that CAA may also play a role in hemorrhage in patients with more evident risk factors. The structural changes in the vascular wall related to CAA are associated with fibrinoid necrosis, focal vessel wall fragmentation and microaneurysms, which all predispose to blood vessel leakage.…”
Section: Discussionmentioning
confidence: 90%